2015
DOI: 10.1037/a0039244
|View full text |Cite
|
Sign up to set email alerts
|

Social media: A contextual framework to guide research and practice.

Abstract: Social media are a broad collection of digital platforms that have radically changed the way people interact and communicate. However, we argue that social media are not simply a technology but actually represent a context that differs in important ways from traditional (e.g., face-to-face) and other digital (e.g., email) ways of interacting and communicating. As a result, social media is a relatively unexamined type of context that may affect the cognition, affect, and behavior of individuals within organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
354
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(368 citation statements)
references
References 123 publications
(173 reference statements)
4
354
0
10
Order By: Relevance
“…Likewise, negative social reactions toward rape victims reduce perpetrator blame and reduce the willingness of individuals to support rape victims more broadly (Brown and Testa 2008: 496). The spread within networks of attitudes, emotions or ideas until they are seen as collective behaviour (known as social contagion theory) is, according to (McFarland and Ployhart 2015), enhanced by social media. Further, the spread of negative responses to sexual assault in an online environment could prevent victim supportive attitudes from being communicated in online spaces, effectively silencing individuals who do not adhere to rape myths.…”
Section: Rolling Stone and Sexual Assaults At Uvamentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, negative social reactions toward rape victims reduce perpetrator blame and reduce the willingness of individuals to support rape victims more broadly (Brown and Testa 2008: 496). The spread within networks of attitudes, emotions or ideas until they are seen as collective behaviour (known as social contagion theory) is, according to (McFarland and Ployhart 2015), enhanced by social media. Further, the spread of negative responses to sexual assault in an online environment could prevent victim supportive attitudes from being communicated in online spaces, effectively silencing individuals who do not adhere to rape myths.…”
Section: Rolling Stone and Sexual Assaults At Uvamentioning
confidence: 99%
“…It has been suggested that this form of news reporting has had negative effects on juries' attitudes towards victims of sexual violence (Fraser 2015;Kitzinger 2013). Previous research has considered how sex crimes are reported by traditional media (Greer 2003;Kirtley 2011;Smolkin 2011); however, the rise of social media and bloggers as information sources means that the popular consumption of, and interaction with, news is changing (McFarland and Ployhart 2015;Salter 2013). Whereas traditionally the media required the public to be passive consumers of news after events had unfolded, real-time online interaction has turned the public into active participants in narrative construction, either through commenting and collaboration or through contributing images and videos as eyewitnesses.…”
Section: Introductionmentioning
confidence: 99%
“…There is also an emerging trend of integrating mobile technologies, SM and learning design (Churchill et al, 2014). Some authors (Derks & Bakker, 2013) assert that SM has revolutionised the way in which people connect, communicate and develop relationships, which is supported by McFarland and Ployhart (2015), who argue for scholarly guidance to provide principles and best practices to capitalise on the possible educational applications of SM. Internet users use SM to upload photos, post blogs, update their status, share files and so forth.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…However, Kietzmann et al (2011) go further by identifying seven building blocks of SM, namely identity, conversations, sharing, presence, relationships, reputation and groups. McFarland and Ployhart (2015) back up the dynamic nature of social interactions on SM sites by arguing that SM represents an extreme form of context that is very different from the non-digital context and some other forms of digital communication media that is based on Web 1.0 technology. The authors suggest eight discreet ambient stimuli of SM that are likely to directly influence the nature of relationships among cognitive, affective and behavioural constructs and processes, which are physicality, accessibility, latency, interdependences, synchronicity, permanence, verifiability and anonymity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…To start with, a key premise of a modular approach is that social media are not seen as an all-in-one technology (i.e., a black box) but rather as a collection of predictor method factors (see also McFarland & Ployhart, 2015). Social media content differs among others in terms of stimulus format (e.g., posting of texts, voice messages, pictures), information source (self-reports vs. endorsements and comments posted by others), stimulus presentation consistency (fixed sets of questions as in LinkedIn vs. free stimuli in Facebook), response evaluation consistency (extraction of social media content by recruiters vs. by machine-learning algorithms), and instructions (social media platforms as weak vs. strong situations).…”
Section: Instructionsmentioning
confidence: 99%